Delivering NICE Joint Pain Advice in the workplace. (2nd March 2021) - Hurley, Michael V.; Irwin, Sally; Erwin, Jo; Gibney, Amber; Hallett, Rachel; Carter, Andrea; Woolf, Anthony
Abstract: Background: Chronic joint pain is extremely prevalent, but its impact can be mitigated if people receive self‐management/lifestyle advice, especially about the importance of physical activity and maintaining a healthy weight. To reach the large number of people who needs support, we devised Joint Pain Advice (JPA), an intervention that can be delivered in a variety of health and community settings by a range of healthcare and non‐healthcare professionals. Here we extend JPA delivery into workplace settings. Method: In each workplace, an advisor was trained to deliver JPA. This involved an initial assessment of participant's pain, musculoskeletal health and function (MSK‐HQ), number of days/week active for >30 min, and physical function. Participants were taught simple self‐management strategies, encouraged to adopt healthier lifestyles using motivational interviewing, goal‐settings and personalised action/coping plans. Participants were reviewed three times over 6 months, baseline outcomes reassessed, progress highlighted, health messages reinforced and action plans revised, if necessary. Results: Twenty large public organisations or small/medium enterprises delivered JPA to 481 people. Satisfaction with the service was high; people found it acceptable, valued advice tailored to their individual needs and experienced tangible benefits—MSK‐HQ (9.5 points; CI 8.3 to 10.6), pain (−1.7; −2.2 to −1.7), physical function (−2.0; −2.2 to −1.7), activity levels and self‐confidence improved, whilst absenteeism and healthcare utilisation reduced. Conclusion: Delivering advice about self‐management for chronic knee, hip and back pain in workplace settings using local health promotion or occupational health professionals and is practicable, beneficial and valued. JPA could benefit small, medium and large employers.